TRAINING IN THE UTILIZATION OF BROILLER CHICKEN - Muhammad Yassir (Jurnal Pengabdian Bangsa, 2025)
Lately, the growth in the need for animal meat, namely broiler chickens, has increased among the people of Aceh in particular and Indonesia in general. Fulfillment of meat needs also results in side effects caused when the fattening process occurs. With the high amount of chicken meat production, the waste from animals also increases linearly and will cause health effects to the community if not handled properly. The thing that appears in general in chicken farming is the odor caused by NH3 gas, H2S, and other elements. Then usually flies will also be more and more, and this will disturb the environment. The Independent Service Team from Syiah Kuala University is trying to find solutions to this problem. Then, socialization activities to the Aceh Jaya farmer group were carried out on June 27, 2021 and also conducted to establish cooperation in the form of providing information on how to handle chicken waste. There are several activities carried out by the socialization team from USK, namely forming a network, providing knowledge about healthy industrial ecology, socializing waste processes, and demonstrating activity processes so that they can be useful to breeder members. The results obtained from this activity are the establishment of network relationships, sharing of industrial ecology knowledge, quality organic fertilizer products, providing greening effects to the environment. It is hoped that this collaboration will not only stop here and in the future we will continue to socialize with different activities in this Aceh Jaya breeder group.